Teachers‟ Attitudes towards Values Across the Curriculum: A Systematic Literature Review - Mohamad, Norliza; Johari Sihes, Ahmad; Mohd Bohari, Normila (International Journal of Psychosocial Rehabilitation, 2020)
Values across the curriculum is an effort to inculcate a moral dimension through school subjects. Based on previous research, teachers' attitudes are very significant to maintain this approach. The purpose of this article is to systematically identify previous studies on teachers' attitudes as the affective domain in successfully implementing values across the curriculum. This review paper was setting two research questions, namely, (1) factors of teachers' attitudes and (2) the challenges of teachers' attitudes. Study inclusion criteria consist of empirical studies that aligned with research questions, published in English, and published between 2009 and 2019. This systematic study applied the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method and has identified 14 related studies using search engines such as Scopus, Dimensions, and Google Scholar to obtain relevant and indexed articles. From the first research question, four themes emerged as factors of teachers' attitudes of values performance, namely, teachers' education, teachers' religious beliefs, teachers' experience, and teachers' socio-political perspectives. From the second research question, two themes emerged as the challenges of teachers' attitudes towards values across the curriculum, which are teachers' competence and teachers’ support. This suggestion of themes is interrelated and indicates that teachers' attitudes are prerequisites for the values across the curriculum implementation. This paper contributes beneficial support to developing strategies for excellence qualities in teachers' attitudes in order to be competent and more functional at handling values issues through subject teaching.